Religious Moderation: An Analysis of Understanding, Internet and Social Media Exposure and Social Interaction Systems - Yuliawati, Elly; Asri, Ispawati (Jurnal The Messenger, 2022)
Introduction: Religious moderation is launched because it concerns the order of life of the nation and state, where the internet and social media become a platform for any dynamic public discussion and change perspectives and practices in religious harmony. This study examines access to information about religious moderation through the internet and social media (WhatsApp, Instagram, Facebook, Twitter, Line) as the most widely used platforms in Indonesia and the influence of exposure to its content on understanding and the system of relational interaction among university students.Methods: Explanatory quantitative survey method with factor and regression analysis to explain the dominant factors and the magnitude of the influence of exposure to religious moderation content on students' understanding and interpersonal relationships.Findings: That student quite often access information about religious moderation on social media through WhatsApp and Instagram. Issues related to national commitment, tolerance, intolerance, violence, radicalism, government attitudes, regulations and their consequences, correlate with the dogmatism factor. The findings show that it is not easy to change one's religious beliefs, and this should be respected. So what remains is to find common ground and give a positive impression so that social interactions continue to run normally.Originality: The research presents a novelty in the perspective of communication science on the understanding of religious moderation and its correlation with the interpersonal interaction system in students from non-religious campuses. Where previously religious moderation was widely studied in the perspective of language, civilization, humanity, culture, education and with subjects from religious campuses, especially Islam.